Performance of Local Beef Cattle For Fattening with Sorinfer Feed After A Short Distance Transportation. Issue 1 (1st April 2022) - Aditia, EL; Priyanto, R; Abdullah, L; Dewi, MHKS Panca; Manalu, W
Abstract: A good quality of feed should be fed to the animal after transport. The objective of the research was to investigate the effect of sorinfer and commercial concentrate feed on feedlot performance of local beef cattle after short period of transportation. This study used 8 Ongole Crossbreed (PO) and 8 Local Crossbreed Cattle (SL) bull with average age of 18-30 months. The average body weight of Ongole and Local Crossbreed Cattle were 291.5±23.5 kg and 289.0±26.3 kg respectively. The bull was allotted into two treatment of feed namely Sorinfer and commercial concentrate feed. Parameter observed were body weight loss, recovery time, body weight after short fattening period, average daily gain, feed consumption and conversion. A factorial 2 × 2 design was used for data analysis. Result shows that average of body weight loss for both breed was 1, 2%. Furthermore, recovery time for both breed was similar for 10 days. In addition, PO cattle with Sorinfer and commercial concentrate feed has higher body weight gain and final weight (P<0, 05) compare to SL cattle. In conclusion, sorinfer feed was effective for recovery after transport for local beef cattle. However, sorinfer provide lower performance compare to commercial concentrate for short fattening period.